Student/patient: the school perceptions of children with cancer. Issue 5 (20th October 2017) - Boles, Jessika C.; Winsor, Denise L.; Mandrell, Belinda; Gattuso, Jami; West, Nancy; Leigh, Laurie; Grissom, Shawna M.
Abstract: Childhood cancer incidence is rising, affecting a growing proportion of elementary school students. For most of these children, school attendance can be limited by hospitalisations, treatments and side effects. However, little is yet known about the educational needs and experiences of this population. This phenomenological study explored the school experiences of 10 6- to 12-year-old children with cancer as they underwent chemotherapy. Results revealed perceptions that attending school in the hospital or home during cancer treatment is essentially lonely, confusing and "different". These perceptions intertwined to illuminate five themes: (1) school should involve fun activities; (2) group educational formats are preferable; (3) old school is the "best school"; (4) being a "good student" is important during treatment; and (5) attending school is complicated during treatment. Therefore, hospital-based and homebound schooling programmes should integrate socially interactive and cognitively engaging curriculum to best support the learning needs of this population.